Luminescence Change from Orange to Blue for Zero‐Dimensional Cs2InCl5(H2O) Metal Halides in Water and a New Post‐doping Method. Issue 12 (11th May 2021) - Yang, Chuang; Guo, Fengwan; Zhang, Yu; Zhong, Xinxin; Feng, Jing; Wang, Nan; Wang, Juan
Abstract: Zero‐dimensional metal halides have attracted much attention due to their attractive photoelectric properties. Here, we propose a new strategy of synthesizing metal halides crystals by recrystallization in water. The as‐synthesized Cs2 InCl5 (H2 O)‐orange crystals are dissolved and recrystallized in water (Cs2 InCl5 (H2 O)‐blue ), with its photoluminescence (PL) changing from orange to blue, both of which are derived from self‐trapping excitons (STEs). The time‐resolved photoluminescence (TRPL) spectrum of Cs2 InCl5 (H2 O)‐blue shows that it has an ultralong lifetime up to milliseconds (τ=52.98 ms), which is expected to be applied in biological sensors. The photoluminescence quantum yield (PLQY) increases from 2.25% to 11.61% in the self‐assembly process. By using a post‐doping method, the PL of crystals turns into red when we introduce Mn 2+ as dopant while there is no obvious change upon using a traditional solvent‐thermal method. Recrystallization in water and post‐doping provide a new perspective for the synthesis and doping of metal halides. Abstract : Cs2 InCl5 (H2 O)‐orange was synthesized through a solvent‐thermal method. When it was dissolved and recrystallized in water, its photoluminescence shifted from 610 blue to 440 nm. Mn 2+ was successfully introduced into the host crystal by using a post doping method in water which cannot be realized by a solvent‐thermal method.